2020
DOI: 10.3390/en13051137
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Flow around a Straight Blade Darrieus Water Turbine

Abstract: In this study, three-dimensional transient numerical simulations of the flow around a cross flow water turbine of the type H-Darrieus are performed. The hydrodynamic characteristics and performance of the turbine are investigated by means of a time-accurate unsteady Reynolds-averaged Navier–Stokes (URANS) commercial solver (ANSYS-Fluent v. 19) where the time dependent rotor-stator interaction is described by the sliding mesh approach. The transition shear stress transport turbulence model has been employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…profiles were used (see references [5,21,33,34]), this interaction was very strong, w directly affected the generated power of the turbine. Although both techniques pred the same behavior of the vorticity, the overset mesh presented a higher resolution, d of the vortices, and unsteadiness of the flow in the near and far wake.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…profiles were used (see references [5,21,33,34]), this interaction was very strong, w directly affected the generated power of the turbine. Although both techniques pred the same behavior of the vorticity, the overset mesh presented a higher resolution, d of the vortices, and unsteadiness of the flow in the near and far wake.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The most relevant metrics of each mesh are summarized in Table 2 . The coarse mesh was built based on reference [ 1 ]; for the fine mesh, the density of elements near the walls of each blade was increased.…”
Section: Geometry and Meshmentioning
confidence: 99%
“…In the analysis, incompressible and isothermal flow is considered, gravitational effects are neglected, and the water is assumed as a Newtonian fluid. Therefore, the governing equations correspond to the averaged mass and momentum conservation equations (Unsteady Reynolds Averaged Navier Stokes or URANS equations) coupled with the k-ω SST turbulence model, while the problem is solved in a transient state, based on the references [ 1 , 18 , 24 ]. Figures 4 and 5 show the boundary conditions in the background and rotational domains, respectively, and Table 5 shows the operational parameters of the simulation.…”
Section: Computational Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al studied the internal flow and performance of the axial flow pump and found that the main part of the pump for energy conversion is the front third of the impeller and the energy conversion capacity of the impeller near the rim is stronger than that of the hub [32,33]. Laín et al revealed that the torque transferred from the fluid to each blade for the Darrieus water turbine was mainly in the upstream semicircle, while such a transfer was very small in the downstream semicircle, and the peak value reduces with the increase of the rotational speed for each blade [34].…”
Section: Introductionmentioning
confidence: 99%